2005
DOI: 10.1177/1096348005276935
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Roles of Service Recovery Strategy: A Relationship-Focused View

Abstract: This study proposed and tested a theoretical model consisting of antecedents and consequences of recovery satisfaction using scenario experimentation with three dimensions of justice manipulated at two levels each (2x2x2 factorial design). Each participant was provided the same service failure (overcooked steak) scenario and one of the eight recovery scenarios (a combination of dimensions of justice). Structural equation modeling was used to test the hypotheses based on 286 cases. All three dimensions of justi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
138
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(160 citation statements)
references
References 71 publications
(205 reference statements)
16
138
1
5
Order By: Relevance
“…Perceived safety and satisfaction service recovery (ȕ=0.043, t=13.072, p<0.000), were all supported. Consistent with prior research on the significant relationship between procedural justice and satisfaction service recovery (Ok et al 2005). Perceived safety and satisfaction (Ringle et al, 2011).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Perceived safety and satisfaction service recovery (ȕ=0.043, t=13.072, p<0.000), were all supported. Consistent with prior research on the significant relationship between procedural justice and satisfaction service recovery (Ok et al 2005). Perceived safety and satisfaction (Ringle et al, 2011).…”
Section: Resultssupporting
confidence: 75%
“…It is not unexpected to find that there is a significant relationship between the independent variables because safety issues like proper check on pilot competence, safety check of aircraft and its appearance should naturally enhance passenger satisfaction with service recovery. Procedural Justice issues are as well understood to influence the satisfaction of aggrieved passengers' satisfaction with the recovery process as suggested by Ok, Back, and Shanklin, (2005) that showed procedural justice of restaurant customer had greater influence on satisfaction service recovery than the other two justices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have found that all three forms of justice including distributive justice, procedural justice, interactional justice have a positive effect on overall service recovery satisfaction (Patterson et al, 2006;dos Santos & Fernandes, 2008;Kim et al, 2009;Karande et al, 2007;Karatepe, 2006;Ok et al, 2005;Smith et al, 1999;Tax et al, 1998;Clemmer & Schneider, 1996;Kau & Loh, 2006). The effects of dimensions of justice on customers' recovery satisfaction have been studied in different service industries as well, including, hotel customers, (Karatepe 2006), mobile phone buyers (Kau & Loh 2006), Undergraduate students, hotel customers (Smith et al, 1999) and Airline passengers (McCollough et al, 2000).…”
Section: Perceived Justice and Recovery Satisfactionmentioning
confidence: 99%
“…Existing strong relationship between a buyer and its suppliers, suppliers tend to support this relationship in long term, even if they lose in short term (Ha and Jang, 2009;Ok et al, 2005). In fact, the level of customer satisfaction and their future behavioral intentions depend on their perceptions to whether they are treated fairly (McColl-Kennedy and Sparks, 2003).…”
Section: Long-term Orientationmentioning
confidence: 99%